(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Target The present work is a study of the significance of clinical and neurological symptoms and an assessment of the effectiveness of using various methods of plastic surgery for post-traumatic defects of the cranial vault.